PENDIDIKAN BERBASIS AKIDAH PADA TK ISLAM TERPADU AZ-ZAHIRA MEULABOH: Implementasi model evaluasi goal oriented pendekatan Robert L. Hammond - Khaidir Khaidir (Jurnal Ilmiah Didaktika, 2015)
Education based on aqidah (faith) is not understood as believe in pillar of faith only, but it is also understood and implemented all the commands of Allah and worshipping him. This study aims to find out the achievement level of faith-based educational program at kinder garten Az-Zahira, Meulaboh, Aceh Barat. The result showed that not all goals of the program in Az-Zahira kinder garten could be achieved. The students’ cognitive, affective, and psychomotoric abilities were not improved as expected. There are several factors that causes it such as: the learning organization was not optimally done, the role of superintendant was not implemented maximally, and the role of parents were still minimum.